Developments since the Fourth WTO Ministerial Conference : market access for non-agricultural products (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Provides a background to the topic and lists mandated deadlines. Focuses on the current state of play, highlighting the following issues, tariff peaks and escalation; non-tariff barriers; EU advocating flexible approach and US zero tariff proposal. Looks at the issue of environmental good and notes implementation concerns.
Keywords: TRADE NEGOTIATIONS